Disorganized attachment in young adulthood as a partial mediator of relations between severity of childhood abuse and dissociation. Issue 4 (7th August 2016) - Byun, Sooyeon; Brumariu, Laura E.; Lyons-Ruth, Karlen
ABSTRACT: Disorganized attachment has been proposed as a mediating mechanism in the relation between childhood abuse and dissociation. However, support for mediation has been mixed when interview or self-report measures of attachment have been used. In the current work, relations among severity of abuse, attachment disorganization, and dissociation were assessed in young adulthood using both interview and interaction-based measures of attachment. A total of 112 low-income young adults were assessed for socioeconomic stresses, abusive experiences in childhood, and attachment disorganization at age 20. Attachment disorganization was assessed with the Adult Attachment Interview, coded independently for Unresolved states of mind and for Hostile-Helpless states of mind. Attachment disorganization was also measured using a newly validated assessment of young adult–parent interaction during a conflict discussion. Mediation analyses revealed that the link between childhood abuse and dissociation was partially explained by disturbances in young adult–parent interaction. Narrative disturbances on the Adult Attachment Interview were related to abuse and to dissociation but did not mediate the link between the two. Results are discussed in relation to the role of parent–child communication processes in pathways to dissociation.